RIGHT OF ACCESS TO AREA OF DEPRECIATED LAND REGULATION WITH THE LAW PERSPECTIVE OF LAND REGISTRY IN INDONESIA - Wulansari, Rizky Juliani; Qamariyanti, Yulia; Erlina, Erlina (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2019)
A Holder of Right has rights and obligation in using his/her land. One of the obligations of a Holder of Right is providing access right to an area of land depreciated which borders with his/her land. The obligation is one manifestation of social function basis. In the social reality, a legal issue pertaining to access to the area of land depreciated bordering with the land ownership. The emerging law issue is the cancelation of Certificate of Right to Own with the issuance basis by taking for granted access right of area of land depreciated and violation of access to area of depreciated land deemed to be an act contradicting the law. The present study is a normative law research. The law research conducted began with inventorization of laws and regulations, judicial decree, governance or other references concerning right of access to an area of depreciated land to be further applied in the relevant cases. There are some legal vacuums (rechtsvacuum) concerning the obligation of Certificate of Right to Own to provide right of access to the area of land depreciated in accordance with the law perspective of land registry in Indonesia. The governance of right of access to area of land depreciated in the laws and regulations in Indonesia is merely stated in Article 13, 31 and 50 of The Government regulation Number 40 of 1996 concerning Right To Cultivate, Building Rights on Land and Right Over Land. The legal solution that can be applied in the relevant issues concerning the obligation of Certificate of Right to Own Holder to provide right of access to an area of depreciated land in Indonesia in by making a separate governance stated in the Laws of Right to Own. In some cases of area of land depreciated cases which have been decided by court, Judge has different consideration and multi-interpretations on the dispute settlement